Spontaneous Rectus Sheath Hematoma Mimicking Bladder Tamponade: A Case Report - Yupeng Wang; Jingyu You; Runzhe Wang; Yeqing Mao; Xiaoyi Chen; Baiye Jin; Guanghou Fu (Journal of Clinical Medicine, 2026)
Background: Spontaneous rectus sheath hematoma is a known but relatively rare complication of anticoagulant therapy. Because its clinical features are similar to various intra-abdominal pathologies, it is often misdiagnosed as other types of acute abdomen in emergency settings. Case Presentation: The patient presented with acute lower abdominal pain, suprapubic distension, and sudden anuria following anticoagulation therapy. Abdominal computed tomography revealed a giant pelvic mass mimicking a distended bladder, suggestive of bladder tamponade. A percutaneous cystostomy was then performed, which, however, drained a large volume of non-clotted blood rather than blood clots. Subsequent radiological and clinical evaluation confirmed a giant spontaneous rectus sheath hematoma. Given the patient’s critical condition and poor prognosis, after thorough discussion with the family, the decision was made to transfer the patient to a local hospital for continued supportive care. Conclusions: This case highlights the diagnostic challenges of giant or atypically located rectus sheath hematomas, which may clinically and radiologically mimic intra-abdominal or urological emergencies such as bladder tamponade. Conventional clinical evaluation and erroneous radiological interpretation can lead to a misdiagnosis, occasionally resulting in inappropriate invasive interventions. Recognizing specific radiological signs, such as internal fluid layering and extravesical catheter placement, combined with multiplanar computed tomography reconstruction, helps minimize diagnostic pitfalls, prevent unnecessary procedures, and optimize clinical outcomes.